Bridging Policy and Practice: Implementation Gaps in Law Number 14 of 2005 on Teachers and Lecturers during the Merdeka Curriculum Era - Ari Kartiko; Mauhibur Rokhman; Muhammad Anas Maarif; Akhmad Sirojuddin; Sahnoza Kayadibi (NAJAHA, 2026)
This study examines the implementation gaps in Indonesia’s Law Number 14 of 2005 on Teachers and Lecturers within the context of the Merdeka Curriculum and the rapid transformation of digital education. Despite formally recognizing teachers and lecturers as professional educators, persistent discrepancies remain between regulatory expectations and educational realities. This research employs a thematic policy document analysis of the primary legal framework, 12 implementing regulations, and 25 academic and policy documents published between 2005 and 2026. The analysis identifies four major implementation gaps: 1) the bureaucratic and inequitable nature of teacher certification and professional development systems; 2) inconsistencies in welfare distribution and legal protection mechanisms; 3) misalignment between centralized legal frameworks and the flexible orientation of the Merdeka Curriculum; and 4) regulatory limitations in addressing digital transformation, artificial intelligence, and post-pandemic educational challenges. The findings reveal that the law continues to operate within a predominantly administrative paradigm, limiting its responsiveness to contemporary educational demands. This study contributes to the literature by integrating legal analysis with contemporary educational policy transformation, while highlighting the urgent need for adaptive and future-oriented regulatory reform. The study recommends revising the existing legal framework to strengthen teacher protection, contextualize professional development, and integrate digital competencies into national education policy.